MODELS TO COUNTER INFORMATION ATTACKS - Дудатьєв, Андрій Веніамінович (Ukrainian Information Security Research Journal, 2015)
The concept of information security should be consideredfrom the complex information security evaluating andproviding in an information warfare point of view. Infact, the need for special information operations performingspecific technologies are stated during complex informationsecurity systems design, implementation andmaintenance. The experience of recent years and eventsshows that the information weapon usage effectiveness inmodern conditions of society informatization is tremendousand their quantitative indicators can be compared tothe weapon of the mass destruction. Two mathematicalmodels are presented to assess information influencepower considering source peculiarities and to proposemanagement solutions for training and further specialinformation counteractions implementations. Analysis ofthe proposed models allowed to formulate generalizedstages of the technique for effective management solutionsfor information security at the facility protection inthe information war.